Sustaining food security in the Karst Mountains through increasing household income: a case study of Gunungkidul Indonesia. Issue 1 (1st December 2022) - Antriyandarti, E; Barokah, U; Rahayu, W
Abstract: One of the poverty areas in Indonesia is in Gunungkidul district, an arid area in the karst mountain area. The scarcity of surface water is the main obstacle to economic development activities in the Karst Mountains of Gunungkidul, especially for agriculture and animal husbandry. The vulnerability of nature, agro-climate, and geographical conditions are not suitable for agricultural economic activities. The income of the agricultural community in the karst mountain area is minimal, which causes high poverty. The highly volatile rainfall in the region and extreme climate change can be destructive. Hence, poverty occurs in Gunungkidul, where dry land and Karst Mountains dominate geographical conditions exacerbate this condition. This study investigates the pattern of household expenditure and analyzes the factors that increase household income. This study applied descriptive analysis and income determination function. The results showed that more than half of household expenditure was for food needs. Non-farming activities have a high contribution to household income. Therefore, to increase household income, households must engage in off-farm jobs. The higher the household income, the food security will be sustained.